MANUFACTURING INDUSTRIAL POLICY DEVELOPMENT POLICY FOR ELECTRIC PROPULSION TO IMPROVE LOCAL CONTENT OF RAILWAY INDUSTRY - Setyo Margo Utomo; Agus Krisnowo (Majalah Ilmiah Pengkajian Industri, 2020)
To fulfill the demand for a number of railroad products, the national railroad industry, in this case PT. INKA as a train integrator industry in Indonesia still has to import components. TKDN electric train is still low. For this reason, it is time to prepare the industrial development of the national railway propulsion system components and even have a very urgent nature. Railway propulsion systems can be classified into three groups, namely: Electric propulsion systems, Diesel Electric propulsion systems and Diesel Hydraulic propulsion systems. Import dependence, of course, cannot be allowed to continue because it will weaken the competitiveness of the national railroad industry. From the results of the analysis using the "Porter Diamond Condition" method various internal and external factors were identified through the SWOT method to formulate alternative policy formulations for the development of the railroad electric propulsion system industry in Indonesia. Qualitative SWOT data are developed quantitatively through the calculation of SWOT Analysis so that the exact position of the organization is known. From the results of the analysis, and calculations using the SWOT Method, the position of the railway propulation system industry is in the Quadrant IV position, so it is best to use a Defensive Strategy. In this position the Company faces a very unfavorable situation, the company faces various threats and internal weaknesses. For this reason, it is necessary to prioritize strengthening strategies in the Matrix (W-T). Key Words: Electric propulsion; Industrial development; Strategy